Competitive binding of transcription factors underlies flexibility of T peripheral helper cells and T follicular helper cells in SLE. (22nd February 2022) - Jiang, Qinglian; Wang, Jiakai; Jiang, Hongkun; Li, Wei; Sun, Yini; Shan, Yu; Wei, Tong; Chi, Xuyang; Yu, Shihan; Ma, Xiaoxue
Abstract: Objective: Peripheral helper T (Tph) cells interact with B cells and promote immune responses at sites of ectopic lymphoid structures (ELSs). To assess the characteristics of Tph cells, we investigated the phenotype of T helper (Th) cells in patients with SLE and the underlying competitive binding mechanisms using cytokine-mediated signal transducer and activator of transcription (STAT) factors. Methods: Peripheral blood mononuclear cells from SLE patients and healthy controls were analysed for phenotypic identification. Serum cytokine levels were detected using Luminex assays. In vitro culture was performed to assess cytokine-induced conversion of phenotypes and transcriptional regulation using flow cytometry and PCR. Chromatin immunoprecipitation was used to evaluate STAT binding and histone modifications. Results: CXCR5 − PD-1 + Tph-like cells were increased in SLE patients and showed strong association with disease activity and renal involvement. Serum IFN-α levels were increased and associated with Tph frequency. IFN-α promoted the differentiation of IL-10-producing CXCR5 − PD-1 + Tph-like cells, increased the responsiveness of IL-2 and induced the conversion of Tfh-like cells to Tph-like cells. STAT5 gained a competitive advantage and bound to the BCL6 locus at the expense of STAT1, accompanied by suppression of H3K4me3. Finally, anti-IFNAR1 decreased the differentiation of Tph-like cells, thereby suppressing the generation of CD38 high CD27 high plasmablasts. Conclusion: Tph cells might be crucial makers to effectively reflect disease activity level in SLE patients. The finding that synergy of IFN-α and IL-2 increases Tph cells through competitive transcriptional regulation could be one of the mechanisms responsible for pathological formation of ELSs and helpful for selection of individualized therapeutic approaches for SLE. Graphical Abstract: